Teachers' cognitions of corrective feedback on pronunciation: Their beliefs, perceptions and practices. (August 2019) - Couper, Graeme
Abstract: There has been research on teachers' cognitions of corrective feedback (CF), their knowledge, beliefs and attitudes and how they are reflected in practice (Borg, 2003; Yoshida, 2010). However, there has been very little attention paid to teachers' cognitions of feedback on pronunciation. The data reported here is based on semi-structured interviews (N = 19) and classroom observations (N = 6) of English as a second language teachers in New Zealand. In an earlier survey, the author had found most pronunciation teaching was ad hoc and in response to errors. Most teachers provided CF, usually through recasts and follow-up listen-and-repeat practice, although other techniques were also reported. The interviews reaffirmed these findings and provided a more in-depth picture, especially with regard to correction techniques, how effective they were believed to be, and the importance of encouraging learner autonomy through peer and self-correction. From classroom observations of six interview participants on two occasions each with follow-up discussions, four key themes emerged: what teachers correct (phonemes and words), how they correct, timing and rationale for CF, and their beliefs regarding sources of errors. They also reveal gaps in teachers' knowledge and training and a need for further research into precisely what makes CF effective.